Digitalisasi dalam Penganggaran Dana Desa: (Studi Kasus pada Pemerintah Desa Lakuan Toli-toli, Sulawesi Tengah) - Virgina Agnesia; Nina Yusnita Yamin; Muhammad Ansar; Latifah Sukmawati Yuniar; Arif Gunarsa (Pusat Riset dan Inovasi Nasional, 2025)
Village financial management is a crucial pillar for village development and community empowerment. This research aims to conduct an in-depth analysis of the village fund budgeting process at the Lakuan Village Government, Tolitoli, Central Sulawesi. Using a qualitative method with a case study research design, data was collected through in-depth interviews with the village head, village secretary, Village Consultative Body (BPD), hamlet heads, head of financial affairs, and community representatives. Informant selection was conducted purposively, based on their involvement in the village fund budgeting process, totaling 8 individuals from the village apparatus and the community. The results show that the village fund budgeting process in Lakuan Tolitoli has been allocated according to the real needs of the community, with active community participation and the BPD serving as an effective oversight mechanism. The use of the Village Financial Information System (Siskeudes) has significantly eased the budgeting process for the village apparatus. This digitalization not only implies an increase in the accountability of village financial management but also serves as an effective control instrument in budget implementation. These findings underscore the importance of multi-party participation and technology adoption in realizing transparent and accountable village financial governance..